Race, Tea and Colonial Resettlement Imperial Families, Interrupted - McCabe, Jane (Bloomsbury Academic, 2017)
Historian Jane McCabe leads us through a compelling research journey that began with uncovering the story of her own grandmother, Lorna Peters, one of 130 adolescents resettled in New Zealand under the scheme between 1908 and 1938. Using records from the 'Homes' in Kalimpong and in-depth interviews with other descendants in New Zealand, she crafts a compelling, evocative, and unsentimental yet moving narrative - one that not only brings an untold part of imperial history to light, but also transforms previously broken and hushed family histories into an extraordinary collective story. This book attends to both the affective dimension of these traumatic familial disruptions, and to the larger economic and political drivers that saw government and missionary schemes breaking up Anglo-Indian families - schemes that relied on future forgetting.